2005
DOI: 10.1093/nar/gki744
|View full text |Cite
|
Sign up to set email alerts
|

DNA-dependent conversion of Oct-1 and Oct-2 into transcriptional repressors by Groucho/TLE

Abstract: POU domain proteins contain a bipartite DNA-binding element that can confer allosteric control of coactivator recruitment. Dimerization of Oct-1 and Oct-2 on palindromic response elements results in the conformational dependent inclusion or exclusion of the transcriptional coactivator OBF-1. In this paper, we demonstrate that Oct-1 and Oct-2 can function as transcriptional repressors by recruiting and physically interacting with members of the Grg/TLE family of corepressors. In accordance with a model of DNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Previous studies have shown that transcription can be repressed directly by prevention of binding of activators to DNA or by interaction with the basal transcriptional machinery. This results in at least two, possibly coordinated, processes that involve inhibition of the RNA polymerase II complex and chromatin remodeling, respectively (1,5,7,42,57). In the in vitro system, a complex of TLE2, RTA, and RRE was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that transcription can be repressed directly by prevention of binding of activators to DNA or by interaction with the basal transcriptional machinery. This results in at least two, possibly coordinated, processes that involve inhibition of the RNA polymerase II complex and chromatin remodeling, respectively (1,5,7,42,57). In the in vitro system, a complex of TLE2, RTA, and RRE was observed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TLEs are broadly expressed nuclear factors that lack intrinsic DNAbinding activity and interact with a variety of DNA-binding proteins. In invertebrates and vertebrates, Groucho/TLE family members have been shown to interact with multiple transcription factors, such as Tcf/HMG box transcription factors, Runt domain proteins, HES proteins, Hesx1, NF-B, PRDI-BF1, PU.1, HNF3b, Hex, Oct-1/Oct-2, and the androgen receptor (AR) (3,25,42,44,54,59,66,78). By recruitment of specific gene-regulatory sequences, Groucho/TLE can downregulate the expression of target genes of transcriptional activators, enhance the transcriptional repression effect of transcriptional repressors, or convert transcriptional activators into repressors (43,57).…”
mentioning
confidence: 99%
“…However, in this report, we demonstrate that a mutant Grg4 protein, in which the GP-domain has been deleted, remains capable of repressing Otx2-induced transcription as efficiently as wild-type Grg4. This suggests that, as in the case of Grg4-mediated repression of Pax2 and Oct-2 activation (61,62), repression occurs via a HDAC-independent mechanism. In the case of Pax2, phosphorylation of Pax2 by c-Jun N-terminal kinase is blocked by association with Grg4, decreasing the transcriptional activity of Pax2.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, Oct-1 also interacts directly with herpes simplex virus (HSV)-and varicella-zoster virus (VZV)-encoded tegument proteins (VP16 and ORF10, respectively), and this interaction is required for the efficient activation of the HSV and VZV immediate-early promoters (34,45,46,58,93). While Oct-1 and the related POU domain transcription factor, Oct-2, have been previously suggested to play a role in regulating the type of EBV latency (3,55,90), neither protein has been shown to play a role in EBV lytic reactivation.…”
Section: Epstein-barr Virus (Ebv) or Human Herpesvirus 4 (Hhv4)mentioning
confidence: 99%